Social Science : an introduction to the study of society - Hunt, Elgin F.; Colander, David C. (Boston, Massachusetts : Pearson Education Incorporation, 2014)
Social science is taught in diverse ways. Some courses take a global perspective, some an anthropological perspective, some a psychological perspective, some a sociological perspective, and some a historical perspective- to name just a few.
Part I. Introduction -- Part II. Culture and the Individual -- Part III. Institutions and Society -- Part IV. Politics and Society -- Part V. Economics and Society -- Part VI. Global Issues.
Includes index.
Keywords: SOCIAL SCIENCES -- TEXTBOOKS